MoveRC - attention-aware remote control - Chagas, Daniel Almeida; Furtado, Elizabeth Sucupira (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
The progress of information technology has made objects continuously acquire new resources and communication skills, therefore we have to change the way we interact with them. As the mainstream media of the twentieth century, television has also followed this trend. TV is changing from a passive medium, from which the viewer only receives information, into an active media, with which there is interaction facilitated by the option of choice, participation and even creating new content. However, the experience of interactive television is often barred by the problems inherent to dealing with the remote control. Especially, when it comes to a task, that is too complex to be done with a standard remote control: the task of putting data in text format into the TV. This paper presents an ongoing research that addresses the input of text data in digital television proposing an attention-aware system.